Pendampingan dalam Pendaftaran Dokumen Kependudukan Secara Online di Kelurahan Bulak Kota Surabaya - Karina Dora Margaretha Am'una; Hertati, Diana (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Implementation of community service activities with assistance in online registration of population documents as an effort to update population data in Bulak Village, Surabaya City. This activity is carried out as a way of national development, the aim is to improve an orderly society in population administration in order to realize. This community service activity is carried out to assist in online registration of population documents as an effort to update population data, starting with population administration services in Bulak Subdistrict and preparing a list of people who have not had orderly population administration. The next activity is assistance in registering population documents at the RW Hall by providing guidance regarding the requirements and procedures for registering population documents through KNG. The final activity carried out was going door to door to residents' homes with the aim of finding out the obstacles experienced by residents who do not have population documents, then providing solutions. After assistance, the majority of people applied to be registered through KNG in order to have population administration documents, so that there was an increase in the number of people in Bulak Village in registering population documents, because residents felt helped in getting their rights to obtain services easily, quickly and free of charge